A study on the sufficiency of legal protection for victims of domestic violence in Malaysia / Hanizah Morni...[et al.] - Morni, Hanizah; Jusoh, Nur Ellyani; Kota, Nurulnita (2006)
Domestic Violence is a form of violence that includes physical and sexual assault, sexual harassment, psychological abuse, or emotional abuse. Although there have been cases where the victims of domestic violence are men, most of the time the victims are women while the perpetrators are men i.e. the victim's husband, father, brother or son. As provided under the Domestic Violence Act 19941, 'domestic violence' means the commission of any of the following acts: (a) wilfully or knowingly, placing or attempting to place, the victim in fear of physical injury; (b) causing physical injury to the victim by such act which is known or ought to have been known would result in physical injury; (c) compelling the victim by force or threat to engage in any conduct or act, sexual or otherwise, from which the victim has a right to abstain; (d) confining or detaining the victim against the victim's will; or (e) with intent to cause, or knowing that it is likely to cause, distress or annoyance to the victim, causing mischief or destruction or damage to property, and protection is not only given to wives but extended to: (i) her spouse; (ii) her former spouse; (iii) a child; (iv) an incapacitated adult; or (v) any other member of the family. Domestic violence normally occurs for a long period and has many effects. The victims may be traumatized physically and mentally and in many cases, the victims do not report it to the authorities. To them, it is better to suffer in silence rather than facing the shame when other people know about their problem. There have been many reports of domestic violence and the number increases by each year. Although some victims may have reported it, it is not clear as to whether the legal protection given to these victims are considered enough and sufficient. Furthermore, there is usually the long delay for protection to be given to victims of domestic violence. An interim prohibitory order is normally given to the abusive spouse long after it is applied for. Thus, instead of stopping harm immediately, because of this delay, even more harm could be made towards the victims.